Targeting the ANGPTL4/NRP1/ABL1/RAD51 axis reverses cisplatin resistance by impairing DNA damage repair in head and neck cancer - Emmanuel B. Asiedu; Ajay Kumar; Alexander Choi; Derek Osorio Luciano; Kevin Lo; Deepti Sharma; Tao Ma; Feyruz Rassool; Akrit Sodhi; Silvia Montaner (Proceedings of the National Academy of Sciences, 2026)
Drug chemoresistance remains a major reason of treatment failure in cancer patients. In head and neck squamous cell carcinoma (HNSCC), the seventh most common cancer worldwide, cisplatin chemotherapy remains the gold standard for advanced tumors but often faces loss of responsiveness and the drawback of relapse. We previously showed that the metabolic and angiogenic factor angiopoietin-like 4 (ANGPTL4) is a molecular biomarker of oral dysplasia and HNSCC. We also found that through interaction with Neuropilin 1 (NRP1), ANGPTL4 activates proliferative and migratory pathways that contribute to HNSCC development. Using HNSCC xenografts, patient tumor-derived organoids, tumor spheroids, and HNSCC cell lines, CAL27, HN13, and HN4, here we provide evidence of the role of ANGPTL4 in the development of platinum-based chemoresistance in HNSCC through the promotion of DNA damage response (DDR) and homologous recombination (HR). ANGPTL4 enhanced these mechanisms by promoting phosphorylation of RAD51 recombinase in Tyr 315/54 through an NRP1/ABL1-dependent mechanism. Pharmacologic inhibition of NRP1 or ABL1 reversed ANGPTL4-mediated DDR and HR, and increased HNSCC cell death in combination with cisplatin, in vitro and in vivo. Our results reveal a role for ANGPTL4 in RAD51-dependent DNA repair and suggest that ANGPTL4/NRP1/ABL1/RAD51 may serve as an alternative therapeutic target for HNSCC.